พฤติกรรมของผู้หญิงวัยทำงานในอำเภอเมือง จังหวัดเชียงใหม่ ต่อการทำศัลยกรรมเสริมความงาม - กนกณัฐ เกรียงชุติมา (เชียงใหม่ : บัณฑิตวิทยาลัย มหาวิทยาลัยเชียงใหม่, 2018)
The objective of this independent study is to study behaviors of working women in Mueang Chiang Mai District towards cosmetic plastic surgery. The samples of this study are working women who live in Mueang Chiang Mai district and had experience to the cosmetic plastic surgery within 1 year. Two hundred questionnaires are used for collecting information. Descriptive statistic was used for data analysis consisting frequency, percentage and mean. From the study, it was found that most of the respondents were 26-35 years old, single, graduated with bachelor degree, private company employees and had income of 10,001-20,000 Baht per month. It was found that the respondents had rhinoplasty the most, by having main surgeon 1 time per year. The average time was 30 minutes – 1 hour. They went to follow up with the surgeon twice by spending time 15-30 minutes. The respondents went to have service on Saturday or Sunday the most. The time they chose to have service was depending on their surgeon’s appointment. The frequency of having service was 1-2 times per year. They paid the service by cash and the average expense was 5,001 – 15,000 Baht per one time. The inspiration of the respondents was to increase their confident and opportunities. The influential persons were acquaintances who used to have surgery. They spent 1-2 months for making decision before having the surgery. The criterion of selecting the surgery clinic was acquaintance’s recommendation. They selected the clinic that was owned by a surgeon. The most of respondents satisfied their cosmetic plastic surgeries and they will return to the previous clinic for the next surgery by having cheeks and jaws surgery the most.